A proanthocyanidin from cinnamomum zeylanicum stimulates phosphorylation of insulin receptor in 3t3-l1 adipocytes - Taher, Muhammad; Abdul Majid, Fadzilah Adibah; Sarmidi, Mohamad Roji (Penerbit UTM Press, 2006)
Non-insulin-dependent diabetes mellitus is due to in large part to insulin resistance, a state where the target cells are no longer responding to ordinary levels of circulating insulin. A drug that promotes the initiation of insulin receptor (IR) signaling by enhancing IR phosphorylation should be useful in the treatment of Type 2 diabetes. To investigate a compound that is able to phosphorylate IR, a proanthocyanidin, cinnamtannin B1, has been isolated from the stem bark of Cinnamomum zeylanicum Blume (Lauraceae). The structure of the compound was established by spectroscopic methods. Cinnamtannin B1 (0.11 mM) activates the phosphorylation of insulin receptor Ã¢-subunit on 3T3-L1 adipocytes. Like insulin, cinnamtannin B1-stimulated phosphorylation of insulin receptor was inhibited by wortmannin, a specific inhibitor of phosphatidylinositol 3-kinase (PI3K) and cytochalasin B, an inhibitor of the glucose transporter (GLUT4); otherwise the phosphorylation was enhanced by vanadate, a tyrosine phosphatase inhibitor. These results suggest that the activity of cinnamtannin B1 is specially mediated by phosphorylation of IR through activation of the PI3K.